Macroeconomic variables affecting share prices in the UAE market ( analytical study ) - Jabbar Musleh, Osama (Opción, 2019)
Despite the novelty of the UAE market for papers currency, but it has become a financed for companies business and the needs of the government sectors , through a variety of financial assets that combine property attribu- tes and attributes of debts, the results of standard analysis of the relationship between the college influential economic variables and the prices of the share market UAE financial showed appropriate monetary school analysis for the conditions of UAE economy as it was a developing economies, and the stocks was partial way of towards the inflation in the short term in the UAE market, and the weakness of the current share prices influenced by the level activity of economy in the subsequent phase, because the connection the level of share prices with the actively speculators and their expectations based on short - term changes, while there was an important effect of the global financial crisis on that market, which required from the UAE central bank to take several measures to stabilize and develop the financial market , avoid and reduce the impact of economic crises